Perencanaan Skenario Program Bantuan Langsung Tunai untuk Mengurangi Tingkat Kemiskinan di Kecamatan Krembangan Kota Surabaya - Agnes Cipta Permatasari; Anggraeny Puspaningtyas; Eddy Wahyudi (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The main issues identified in this study include mistargeting of beneficiaries, weak inter-agency coordination, low community participation in the verification process, and a tendency among recipients to rely on cash assistance in a consumptive manner. This research analyzes the scenario planning of the Cash Transfer Program (BLT) in reducing poverty in Surabaya City, particularly in Krembangan District. The program is implemented based on Surabaya Mayor Regulation Number 130 of 2023, which serves as the legal foundation for the regional BLT scheme. Using the Scenario Planning TAIDA model (Tracking, Analysing, Imaging, Deciding, and Acting) by Mats Lindgren and Bandhold (2003) as the analytical framework, this study examines the extent to which planning, decision-making, and implementation processes are able to respond to the socio-economic dynamics of the community. Employing a descriptive qualitative method, data were collected through interviews, observations, and documentation. The findings indicate that BLT plays a significant role in supporting low-income households and reducing poverty rates; however, challenges persist, including limited community engagement, weak inter-agency coordination, and non-productive use of assistance. The scenario planning approach is considered effective in helping the government design more adaptive, participatory, and sustainable policy strategies. It is expected that the BLT program will not only serve as a short-term intervention but also become a strategic instrument in promoting independence and improving the welfare of poor communities in Surabaya.